Seismic performance of innovative double layer space shear wall - Bayat, Behzad (2014)
Various kinds of seismic structural systems could not completely satisfy engineers due to excessive rigidity and low ductility. Then engineers innovate advanced ductile structural systems like viscous elastic dampers to dissipate earthquake forces and insulate important structural elements in safe zone; however these systems have not been pervasive in construction industry due to high production cost. Indeed, optimization of stiffness, ductility, and construction cost are the major challenges facing the engineering profession in designing a perfect lateral system. This research introduces Space Shear Wall (SpaSW), as an innovative earthquake resistant system for structures and evaluates its feasibility and seismic performance through three-dimensional linear and nonlinear-static, lineardynamic, and finite element analysis carried out by ETABS and ANSYS program. Space shear wall is defined as a double-layer diagonal space frame structure with ball joints vertically used as infill wall. The comparative study between SpaSW and steel bracing used in typical low to high-rise structures expressed that structural drift of SpaSW is slightly higher than steel bracing. However the ductility, energy dissipation, members’ stress and distribution of earthquake force in SpaSW are significantly better than typical steel bracing. In addition, failure mechanism of SpaSW were favourable due to its gradual process through many ball joints. Moreover, lightness, industrialization, maintainability and reparability, compatibility with architectural considerations, low cost, simple and fast fabrication are other realized advantages. Developing this concept would be considered in the future studies through optimization of material, grid patterns, connection, and additional dampers.